Later-Onset Hypertension Is Associated With Higher Risk of Dementia in Mild Cognitive Impairment - Qin, Hongyun; Zhu, Binggen; Hu, Chengping; Zhao, Xudong (Frontiers in Neurology, 2020)
To investigate the correlation between hypertension development and the progression of mild cognitive impairment (MCI) to dementia in middle-aged and elderly people. A population-based longitudinal cognition survey of people aged 55+ was conducted. The hypertension onset age was estimated by self-reported information and medical insurance card records. To study the effect of later-onset hypertension on dementia, the incidence of dementia was compared between the two groups. Of 277 hypertensive MCI participants without dementia, 56 (20.22%) progressed to dementia (MCIp) over the 6-year follow-up. The proportion of MCIp participants in the old-age-onset hypertension group (≥ 65 years) was higher than that in the middle-age-onset hypertension group (27.0% vs 15.4%, respectively; X2 = 5.538, P = 0.019). In the old-age-onset hypertension group, the proportion of MCIp without diabetes mellitus was higher than those with diabetes mellitus (24.7% vs 12.6%, respectively; X2 = 5.321, P = 0.021) and those with increased pulse pressure was higher than those without increased pulse pressure (33.3% vs 15.4%, respectively; X2 = 3.902, P = 0.048). However, the cox proportional hazard showed that older age was the only risk factor for MCIp (HR=0.618, p=0.000). These results suggest that individuals with later-onset hypertension may have greater cognition decline, even with blood pressure maintained at 130/80 mmHg with antihypertensive management.